Trust in AI-Driven Marketing and its Impact on Brand Loyalty: The Mediating Role of Adoption Intention among Generation Z Consumers - Secretaria, Norberto M. (International Review of Management and Marketing, 2026)
This study is primarily focused on the determination of the influence of Trust in AI-driven marketing on Brand Loyalty, with Adoption Intention as a mediating factor among Generation Z consumers. The data were collected from 450 respondents and analyzed through Structural Equation Modeling using SPSS AMOS. The psychometric properties resulted in CFI = 0.980, TLI = 0.974, RMSEA = 0.062, SRMR = 0.031, which demonstrates excellent fit indices confirming the model’s reliability and validity. Results show that trust is a significant predictor of both adoption intention (β = 0.718, p < .001) and brand loyalty (β = 0.410, p < .001), while adoption intention strongly influences brand loyalty (β = 0.717, p < .001). As to the mediation analysis, the result confirmed a significant indirect effect (β ≈ 0.390, p = 0.001), indicating that adoption intention partially mediates the trust–loyalty relationship. The findings of the study present a significant view on the importance of trust in shaping AI-aided marketing and its adoption, leading to loyalty among Generation Z consumers. This study adds to the literature of the Technology Acceptance Model and Relationship Marketing Theory, and provides managerial insights on how brands can enhance customer loyalty through proper implementation of trustworthy AI-driven marketing practices.